India's Vegetable Oil Economy and Consumer Preference for Blended Soybean Oil in South India - Kavitha, V.; Angles, S.; Chinnadurai, M.; Kumarappan, Subbu (Indian Journal of Marketing, 2013)
Oil seeds and edible oils are the essential commodities in Indian trade. Among the edible oils, soybean oil is highly recommended for reducing the level of bad cholesterol in the blood. Though it is used in large quantities in other parts of India, its usage in South India is quite limited. The analysis of growth rate of total oil seeds area in India showed a positive growth of 0.75%, and the production statistics revealed a growth rate of 2.98% per annum . This indicated that there is a need to promote oil seed crops. To promote this protein-rich oil, a study was undertaken in Coimbatore city of Tamil Nadu. The study aimed at analyzing the production and growth of oil seeds in India in general, and Tamil Nadu in particular, and to ascertain the factors influencing the consumers' buying behavior of blended soybean oil by using the logit model. The study revealed that in Coimbatore, soybean oil is sold as blended soybean oil (mixed with other vegetable oils). The major factors which influenced the consumers to purchase soybean oil were age, education, and occupation of the decision maker (regarding the oil to be used for cooking) and health conditions of the entire family.